Polish International Relations Studies and Post-Historiography, Disciplinary Development after the Cold War - Haliżak, Edward (UNISCI Journal, 2016)
The purpose of this article is to present the methodological and institutional development of international studies in Poland, which were formed under the influence of the unique historical experience resulting from Poland’s geographical location between Germany and Russia. This unfavourable geopolitical location was overcome after the Cold War, when Poland joined Western institutions: NATO and the European Union. The integration with the West provided a qualitatively new impetus for the development of international studies and especially the issues of security and European integration; moreover, entirely new possibilities of academic cooperation opened up in the field of international relations studies. The article focuses on the following issues: first, the historical tradition of international relations studies in Poland until the end of the Cold War; and second, the process of autonomisation of international studies in Poland as a discipline of social sciences after the fall of communism.